Fabrication of an Anti-Reflective and Super-Hydrophobic Structure by Vacuum Ultraviolet Light-Assisted Bonding and Nanoscale Pattern Transfer - Yuki Hashimoto; Takatoki Yamamoto (Micromachines, 2018)
The application of subwavelength, textured structures to glass surfaces has been shown to reduce reflectivity and also results in self-cleaning due to super-hydrophobicity. However, current methods of producing such textures are typically either expensive or difficult to scale up. Based on prior work by the authors, the present study employed a combination of vacuum ultraviolet (VUV) light-assisted bonding and release agent-free pattern transfer to fabricate a moth-eye texture on a glass substrate. This was accomplished by forming a cyclic olefin polymer mold master with a moth-eye pattern, transferring this pattern to a polydimethylsiloxane (PDMS) spin coating, activating both the PDMS and a glass substrate with VUV light, and then bonding the PDMS to the glass before releasing the mold. Atomic force microscopy demonstrated that the desired pattern was successfully replicated on the PDMS surface with a high degree of accuracy, and the textured glass specimen exhibited approximately 3% higher transmittance than untreated glass. Contact angle measurements also showed that the hydrophobicity of the textured surface was significantly increased. These results confirm that this new technique is a viable means of fabricating optical nanostructures via a simple, inexpensive process.